Estudio de prefactibilidad para la instalación de una planta productora de granos de caucho a partir del reciclaje de neumáticos en desuso - Sánchez Duany, Roberto Luciano (2019)
The present investigation corresponds to a "Pre-feasibility study for the installation of a rubber-grain production plant from the recycling of disused tires". This is a pioneering and innovative project in tire recycling which has collected the national issues in social and environmental aspects to propose an adequate solution that allows generating economic benefits by being responsible with the environment and society in general. The market research showed that there is a demand of more than 4,000 tons per year that is currently served by various importers. It was found that it would be of interest for consumers to acquire rubber grains from a local supplier that guarantees a quality product at a lower price, conserving the environment and helping to improve it. The plant will be located in Lurín due to the proximity to the market and raw material, main factors of success of the project. Also, the costs for the development of the company are favorable in this location. There are adequate services, workforce and industrial areas suitable for the project. With the capacity of the market, the technology and the optimal start-up plant size were determined. For this we received advice from foreign suppliers specializing in tire recycling solutions who recommended a semi-automatic plant with a capacity of 1 ton per day. This disposition, including warehouses and offices, requires an installation of approximately 1,000 m2. The economic and financial analysis, with an investment of S/ 2 530 029, gave very encouraging indicators. With an opportunity cost of 34.35%, a financial NPV of S/ 1 579 199 and a financial IRR of 112% was obtained, demonstrating the profitability of the project, recovering the investment over a period of two years and two months. Finally, the study of social and environmental indicators showed the importance and benefits of the project and the recycling of more than 2 500 tons in the future, almost 23% of the total that is generated each year that would otherwise take hundreds of years to decompose.